Peripheral Immune Alterations in Major Depression: The Role of Subtypes and Pathogenetic Characteristics - Euteneuer, Frank; Dannehl, Katharina; del Rey, Adriana; Engler, Harald; Schedlowski, Manfred; Rief, Winfried (Frontiers in Psychiatry, 2017)
Depression has been associated with peripheral inflammatory processes and alterations in cellular immunity. Growing evidence suggests that immunological alterations may neither be necessary nor sufficient to induce depression in general, but seem to be associated with specific features. Using baseline data from the Outcome of Psychological Interventions in Depression (OPID)-trial, this exploratory study examines associations between depression subtypes and pathogenetic characteristics (i.e., melancholic vs non-melancholic depression, chronic vs non-chronic depression, age of onset, cognitive-affective and somatic symptom dimensions) with plasma levels of C-reactive protein (CRP), interleukin (IL)-6, IL-10, and numbers of leukocyte subpopulations in 98 patients with Major Depression and 30 age and sex-matched controls. Patients with Major Depression exhibited higher CRP levels, higher neutrophil and monocyte counts, lower IL-10 levels and an increased neutrophil to lymphocyte ratio (NLR) than controls. Patient with later age of onset had higher levels of two inflammatory markers (CRP, NLR) and lower cytotoxic T cell counts after adjusting for sociodemographics, lifestyle factors and antidepressants. Furthermore, lower anti-inflammatory IL-10 levels were related to more severe somatic depressive symptoms. These results confirm and extent previous findings suggesting that increased levels of CRP are associated with a later onset of depression and demonstrate that also NLR as a sub-clinical inflammatory marker is related to a later onset of depression.